If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3 + 3d) + -5 = 6 + -1(2d + 7) (3 * -4 + 3d * -4) + -5 = 6 + -1(2d + 7) (-12 + -12d) + -5 = 6 + -1(2d + 7) Reorder the terms: -12 + -5 + -12d = 6 + -1(2d + 7) Combine like terms: -12 + -5 = -17 -17 + -12d = 6 + -1(2d + 7) Reorder the terms: -17 + -12d = 6 + -1(7 + 2d) -17 + -12d = 6 + (7 * -1 + 2d * -1) -17 + -12d = 6 + (-7 + -2d) Combine like terms: 6 + -7 = -1 -17 + -12d = -1 + -2d Solving -17 + -12d = -1 + -2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '2d' to each side of the equation. -17 + -12d + 2d = -1 + -2d + 2d Combine like terms: -12d + 2d = -10d -17 + -10d = -1 + -2d + 2d Combine like terms: -2d + 2d = 0 -17 + -10d = -1 + 0 -17 + -10d = -1 Add '17' to each side of the equation. -17 + 17 + -10d = -1 + 17 Combine like terms: -17 + 17 = 0 0 + -10d = -1 + 17 -10d = -1 + 17 Combine like terms: -1 + 17 = 16 -10d = 16 Divide each side by '-10'. d = -1.6 Simplifying d = -1.6
| 2+6c=-1+11c | | 5(4w+-20)=4(5w+-25) | | 4x^2-11=12 | | 2x-4*-3=11 | | (1)/(9)(2m-16)=(1)/(3)(2m+4) | | 4w-6-2w=2w-6 | | 2x+4*-3=11 | | [8k+1]-3=3 | | 9(y-9)=8y-1 | | 20w^2-11w-3= | | (n)3/4+5=(n+1)1/2 | | 5x-2x=24-9x | | 8x+2(6-x)=3x+10 | | .2x-.12=1.4 | | 12a^2+4+3a^2-2= | | 7x-8x=4-2x | | 3m+10=2(4m-5) | | -9=3x+12 | | 2.45-3.1t=21.06 | | x^2-40x+100=0 | | 2(2a-23)=-5w-4 | | 13x+11=13x-7 | | .3(12x+3)+4(6x+1)=43 | | 7x+9*6=5+7x | | y+6=22-3y | | 4x^2-45=4 | | (19X^2)+36X-4=0 | | 3y-13=-2y+7 | | 6n-3n=4 | | -6x-4=-2 | | 3a^2+26a+48=0 | | (8x+5)(3x^2-14x-5)=0 |